The rise and fall of the British Empire - James, Lawrence 1943- (St. Martin's Press, 1996)
Great Britain's geopolitical role has undergone many changes over the last four centuries. Once a maritime superpower and ruler of half the world, Britain now occupies an isolated position as an economically fragile island often at odds with her European neighbors. Lawrence James has written a comprehensive, perceptive, and insighful history of the British Empire. Spanning the years from 1600 to the present day, this critically acclaimed book combines detailed scholarship with readable popular history.